1979
DOI: 10.1002/ajpa.1330510111
|View full text |Cite
|
Sign up to set email alerts
|

Browridge structure and function in extant primates and Neanderthals

Abstract: The structural characteristics of the supraorbital ridge in three extent primate species and fossil Neanderthals are described in this study. Surface morphology and patterns of trabecular organization as observed in cross-sectional collections of Pupio, Mucucu and Pun are compared with similar traits encountered in the Pech de 1'Aze infant, Gibraltar child, and La Quina 5, La Chapelle-aux-Saints, Broken Hill, Skhul V, Skhul IX, Tabun I and Gibraltar adult Neanderthals. Periods of rapid appositional growth of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
1

Year Published

1980
1980
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 16 publications
3
29
1
Order By: Relevance
“…Histology also provides insights into the dynamics of bone growth and remodeling over the course of human ontogeny and evolution (e.g. Martin and Armelagos, 1979;Oyen et al, 1979;Abbott et al, 1996;Gosman and Ketcham, 2009). Furthermore, it allows for the development of standards for comparison with other nonhuman primates (e.g.…”
Section: Ontogeny Phylogeny and The Skeletal Response To Biomechanimentioning
confidence: 99%
“…Histology also provides insights into the dynamics of bone growth and remodeling over the course of human ontogeny and evolution (e.g. Martin and Armelagos, 1979;Oyen et al, 1979;Abbott et al, 1996;Gosman and Ketcham, 2009). Furthermore, it allows for the development of standards for comparison with other nonhuman primates (e.g.…”
Section: Ontogeny Phylogeny and The Skeletal Response To Biomechanimentioning
confidence: 99%
“…Previous investigations indicated con trasting developmental sequences in the hominid VP and the nonhuman primate areolar brow surfaces. I n baboon and macaque skulls the fine cancellous surface is found on many immature individuals, ranging in de velopmental age from deciduous dentition to nearly mature, with other immature spec imens of different ages showing a smooth brow surface [Oyen et al, 1979a;1979b; . This indicates that the areolar brow surface alternates with periods of smooth surface during the development of the indi vidual.…”
Section: Introductionmentioning
confidence: 99%
“…Surface structure indistin guishable from the VP of the fossils may also be observed as a variable feature in modern human populations [Tappen, 1978[Tappen, , 1983, although usually with considerably less sur face relief and in lower frequencies than in the fossils. Recently, Oyen et al [1979aOyen et al [ , 1981 have reported an areolar configuration which appears intermittently on the brow surfaces of immature individuals of some nonhuman primate species, identifying this as 'fine cancellous bone', and elsewhere [Oyen et al, 1979b] as 'woven bone'. They have equated this with the fossil hominid VP.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations